(untitled) (Online Journal of Humanities ETAGTSU, 2023)
The seventh issue of the journal “Online Journal of Humanities” includes papers in the following directions: Linguistics, Literature and ELT and Education. Papers in linguistics explore various spheres of discourse analysis and conceptual metaphors. “Multimodal discourse analysis of Sia’s music video “Elastic Heart” by Nato Peradze explores Sia’s music video “Elastic Heart” based on Halliday’s three metafunctions and Machine’s work (2010). The importance of metaphoric thinking and the influence of multimodal metaphors in decoding the overall meaning of an art piece are studied and interesting conclusions are reached. Specifically, the study finds that Sia’s song “Elastic Heart” predominantly employs key conceptual metaphors, namely MENTAL ILLNESS IS A BOUNDED SPACE/DEPRESSION IS A BOUNDED SPACE. Interestingly, these metaphors are “realized simultaneously in two different semiotic modes and highlight the significance of metaphoric interpretation of visual elements in the music video”. In her paper “What is hate speech and why should we study it?”, Sopio Totibadze raises awareness about hate speech, which, sadly, has become a genre characteristic of computer-meditated communication, and discusses the mechanisms to fight against it. Salome Gogadze makes an effort to explore the characteristics of wine discourse in her paper “Georgian winespeak”. This paper verbalizes the features (flavour, aroma, colour..) of wine, and explores and compares metaphors employed while describing the properties of wine in Georgian and English. As well as this, the article compares the lexical means employed while characterising the wine properties in both languages and proposes lexical-semantic equivalents.. In her paper “Learner corpus profiles: lexial peculiarities of Georgian EFL students, Marine Makhatadze focuses on the usability of learner corpus in foreign language research. It is known that teachers, lexicographers and researchers use learner corpus data to measure the most fundamental aspect of second/foreign language knowledge – lexical profiles of the learners. This paper makes an attempt to explore the type of lexical behaviour represented in the learner corpus data, and the potential of giving learners/teachers access to the learners' data. The paper by Tamar Khvedelidze,” Metaphor in copywriting”, explores the creation, functioning and decoding processes of metaphor in this sphere and discusses the results based on the emotional background of a decoder. In this process, the emphasis is placed on the shared background knowledge and a mood of a decoder. The importance of metaphor for creative thinking, the function and significance of metaphor in copywriting are also revealed. In her article “ Comparative linguistic and functional analysis of verbal irony during the COVID-19 pandemic ( usinf examples from English and Georgian Facebook posts), Mari Nikabadze aims to explore the function of verbal irony in social media via comparative analysis through the scope of social and cultural peculiarities revealed in social, cultural, religious, and other characteristics of an individual or a group of people. In the direction of Literature, Lela Ebralidze, in her paper The two sides of Edgar Allan Poe’s personality. Personal Tragedy reflected in his works”, describes the life and works of Edgar Allan Poe and focuses on the personal qualities and his role in the development of various literary genres and enrichment of world literature. Papers published in The ELT and Education discuss significant issues of EFL. Valeria Purtseladze’s paper “Towards the use of the first language in EFL teaching: The students’ perspective” discusses the significance of the grammar-translation method in teaching English as a foreign language from the standpoint of the student’s perception of the issue. Interestingly, the paper is based on the results of the survey conducted among the BA students of TSU. The results of the survey show that despite being considered controversial, the grammar-translation method is still perceived as a useful technique for learning a foreign language by the majority of the respondents. The article by Nino Jojua “Developing democratic culture based on diverse types of education-non-formal education” highlights the benefits of implementing non-formal education at Chkhoria Public School located in Zugdidi municipality village Chkhoria. The author describes positive changes, including a more efficient way of managing time, place and environment, an easier and more efficient method of involving students in their learning process, a more flexible way of giving a freedom of choice. Manana Rusieshvili-Cartledge Editor-in-Chief